2020
DOI: 10.1017/jog.2020.64
|View full text |Cite
|
Sign up to set email alerts
|

Slope estimation influences on ice thickness inversion models: a case study for Monte Tronador glaciers, North Patagonian Andes

Abstract: Glacier ice thickness is crucial to quantifying water resources in mountain regions, and is an essential input for ice-flow models. Using a surface velocity inversion method, we combine ice thickness measurements with detailed surface elevation and velocity data, and derive ice thickness and volume estimates for the Monte Tronador glaciers, North Patagonian Andes. We test the dependence of the inversion model on surface slope by resampling glacier slopes using variable smoothing filter sizes of 16–720 m. While… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…De todos los métodos analizados, el de caja variable es el único que permite capturar potenciales cambios en la relación longitud-área para el glaciar Alerce a lo largo del período estudiado. Por lo anterior, con este método es posible realizar estimaciones de área, y por consiguiente de volumen (Zorzut et al, 2020), utilizando únicamente los datos de posición del frente. Además, es posible ajustar estas estimaciones según la morfología del glaciar.…”
Section: Variaciones En La Relación De Longitud Y áRea Del Glaciar Al...unclassified
“…De todos los métodos analizados, el de caja variable es el único que permite capturar potenciales cambios en la relación longitud-área para el glaciar Alerce a lo largo del período estudiado. Por lo anterior, con este método es posible realizar estimaciones de área, y por consiguiente de volumen (Zorzut et al, 2020), utilizando únicamente los datos de posición del frente. Además, es posible ajustar estas estimaciones según la morfología del glaciar.…”
Section: Variaciones En La Relación De Longitud Y áRea Del Glaciar Al...unclassified
“…Recently, Zorzut et al (2020) calculated the ice thickness distribution of Monte Tronador glaciers and found that the gently sloped debris-covered tongue of the Verde glacier is one of the thicker parts of the whole glaciers of Monte Tronador, with a maximum estimated thickness of around 180 ± 60 m and a total volume of 0.59 ± 0.2 km 3 .…”
Section: Regional Context and Area Of Interestmentioning
confidence: 99%
“…Besides the ice thickness, GPR and RES also provide bedrock topography description, which influences glacier hydrology (Grabiec et al, 2012). Furthermore, bedrock topography is a necessary constraint for developing numerical glacier-flow and rheological models (Faillettaz et al, 2012;Zorzut et al, 2020). It is well known that bedrock geometry determines glacier surface morphology (Paterson, 1994).…”
Section: Introductionmentioning
confidence: 99%